Amplitudes : stories of queer and trans futurity - Mandelo, Lee (Erewhon Books, 2025)
Amplitudes: Stories of Queer and Trans Futurity is a speculative fiction anthology exploring queer and trans lives across imaginative futures--from dystopian cities to galactic nightclubs. Blending protest, desire, and whimsy, the collection reclaims sci-fi as a space for queer liberation, resilience, and radical possibility.